Assessing the impact of COVID-19 at 1-year using the SF-12 questionnaire: Data from the Anticipate longitudinal cohort study. (May 2022) - O'Kelly, Brendan; Vidal, Louise; Avramovic, Gordana; Broughan, John; Connolly, Stephen Peter; Cotter, Aoife G; Cullen, Walter; Glaspy, Shannon; McHugh, Tina; Woo, James; Lambert, John S.
Highlights: Those patients with post–COVID-19 syndrome (PoCS) had reduced 12-item Short Form Survey (SF-12) scores at 1-year. Those with ≥5 symptoms at initial diagnosis had lower SF-12 scores at 1-year. Lower physical composite score (SF-12) at 3 months was predictive of PoCS at 1-year. High heart rate at rest at 3 months was predictive of PoCS at 1-year. Abstract: Background: Few studies to date have explored the health-related quality of life (HRQoL) in patients with long COVID. Methods: The Anticipate Study is a prospective single-centre observational cohort study. Hospitalised and nonhospitalised patients were seen at a dedicated post-COVID clinic at a 2-4 month (Timepoint 1) and 7-14 month follow-up (Timepoint 2). The main objectives of this study are to assess the longitudinal impact of COVID-19 in patients using the 12-item Short Form Survey (SF-12) score, a health-related quality of life tool, and to identify predictors of developing post–COVID-19 syndrome (PoCS). In addition, we aimed to describe symptomatology and identify predictors of PoCS at 1-year. Results: A total of 155 patients were enrolled, 105 (68%) were female aged 43.3 (31-52) years. In total 149 (96%) and 94 (61%) patients completed follow-up at median 96 (76-118) days and 364 (303-398) days. The overall cohort had significantly reduced physical composite score (PCS) of the SF-12 (45.39 [10.58] vs 50 [10], p = 0.02). Participants with PoCS had significantly lower scores than those without symptoms at 1-year follow-up (37.2 [10.4] v 46.1 [10.9] p <0.001), and scores for these patients did not improve over the 2 Timepoints (PCS 34.95 [10.5] – 37.2 [10.4], p = 0.22). Fatigue was the most common symptom. Those with 5 or more symptoms at initial diagnosis had lower PCS and mental composite score (MCS) at 1-year. Predictors of PoCS at 1-year were lower PCS and higher baseline heart rate (HR) at clinic review median 3 months after COVID-19. Conclusion: Patients with PoCS have lower PCS scores during follow-up, which did not significantly improve up to a 1-year follow-up. Lower PCS scores and higher HR at rest can be used in the weeks after COVID-19 can help predict those at risk of PoCS at 1 year.